2021
DOI: 10.5430/rwe.v12n1p267
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development on Employment Rate in Nigeria

Abstract: This study examines financial development on employment rate in Nigeria on the premise of goal 8 of the sustainable development goals (SDGs). Using the ARDL model and annualized time-series data from 1999-2019. Findings revealed a positive and statistically significant impact of financial development on employment rate. Supporting the Phillips curve of an inverse nexus between inflation rate and unemployment rate. The findings contravene Okun’s law of a negative relationship between economic growth and unemplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Since the unemployment rate is an indicator to measure the employment situation of a country, to more intuitively clarify the relationship between green finance and the unemployment rate. Ndubuaku et al (2021) utilize the ARDL model and annualized time-series information from 1999 to 2019 to research the effect of financial development on the employment rate in Nigeria. The result shows that financial development altogether affects the employment rate.…”
Section: Green Finance and Unemployment Ratementioning
confidence: 99%
“…Since the unemployment rate is an indicator to measure the employment situation of a country, to more intuitively clarify the relationship between green finance and the unemployment rate. Ndubuaku et al (2021) utilize the ARDL model and annualized time-series information from 1999 to 2019 to research the effect of financial development on the employment rate in Nigeria. The result shows that financial development altogether affects the employment rate.…”
Section: Green Finance and Unemployment Ratementioning
confidence: 99%
“…Other measures of economic growth, such as financial efficiency, financial liquidity, financial stability, and financial sector credit to the private sector, only reduce unemployment in the short run. Ndubuaku et al (2020) examine the effect of financial development on employment in Nigeria during the 1999-2019 period using the technique of ARDL modeling. The study found that economic development measured as broad money as a percentage of the GDP was positively and significantly related to employment.…”
Section: Financial Developmentmentioning
confidence: 99%